Some Simple Analytics of Trade and Labor Mobility - Artuc, Erhan; Chaudhuri, Shubham; McLaren, John (World Bank Group, Washington, DC, 2014)
This paper studies a simple, tractable model of labor adjustment in a trade model that allows researchers to analyze the economy's dynamic response to trade liberalization. Since it is a neoclassical market-clearing model, duality techniques can be employed to study the equilibrium and, despite its simplicity, a rich variety of properties emerge. The model generates gross flows of labor across industries, even in the steady state; persistent wage differentials across industries; gradual adjustment to a liberalization; and anticipatory adjustment to a pre-announced liberalization. Pre-announcement induces anticipatory flight from the liberalizing sector, driving up wages there temporarily and giving workers remaining there what this paper calls "anticipation rents." By this process, pre-announcement makes liberalization less attractive to export-sector workers and more attractive to import-sector workers, eventually making workers unanimous either in favor of or in opposition to liberalization. Based on these results, the paper identifies many pitfalls to conventional methods of empirical study of trade liberalization that are based on static models.